DYNAMICS OF THE DEVELOPMENT OF EMOTIONAL HEARING THROUGH PLAY IN PRESCHOOLERS WITH HEARING DISABILITIES - CIUBOTARU Natalia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The article represents the summary of a study in which we present the results of the control experiment in the framework of research on the development of emotional hearing in children with hearing disabilities. The current trends regarding the methods of therapeutic intervention in complex psychopedagogical assistance, the use of games as a form of fundamental learning are described. The given study presents the main elements of the training program carried out and the results obtained by children with hearing disabilities in the control experiment that allowed us to demonstrate a positive dynamic of the results received due to the effectiveness of the psycho-pedagogical interventions developed and implemented within the research.